Pola Asuh Permisif dan Perilaku Konsumtif Pada Mahasiswa Bimbingan dan Konseling - Bernike Putri Hadyanti; Yohanes Heri Widodo (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to find the relationship between permissive parenting with consumptive behavior of students in emerging adulthood, to identify the intensity of permissive parenting and the level of consumptive behavior; to know the items of permissive parenting scale and the items of consumptive behavior scale that reached high scores that could be proposed as a topic of guidance. The design of this study is correlational research with a quantitative descriptive approach. A sample subject of this research was 90 students of Guidance and Counseling in Sanata Dharma University those aged 18 – 25 years old. A method of data collection conducted by survey techniques using google form. The result of the correlational hypothesis analysis showed that Pearson’s r value is 0.219 with a significant value of ρ 0.038 (ρ < 0.05). The result showed that there was a significant positive relationship between permissive parenting and consumptive behavior of students in emerging adulthood. The results of permissive parenting achievement show a tendency at low levels, and at the achievement of consumptive behavior shows a tendency at low levels. The proposed guidance topics for high-identified permissive parenting scale items are: Reward vs Punishment, while the guidance topics for high-identified consumptive behavior scale items are: self-control and managing your money wisely.